The effect of blended microlearning soil analysis practicum on students' learning outcomes in Geography - Yurotul Aidah; Ferryati Masitoh (Indonesian Journal of Educational Development (IJED), 2026)
High schools with limited instructional resources require learning approaches that are both effective and practical. This study investigated the effectiveness of a blended microlearning model in improving students' learning outcomes during a soil analysis practicum in Geography. A quasi-experimental posttest-only control-group design was used with 59 Grade XI Social Science students at SMA Diponegoro Tumpang. Two classes were selected through purposive sampling: an experimental group (n = 30) that received blended microlearning instruction and a control group (n = 29) that followed conventional practicum-based learning. Data were collected using a cognitive achievement test, a psychomotor performance rubric, and a learning motivation questionnaire. The results show that students in the experimental group achieved a higher mean score (M = 87.3) than those in the control group (M = 79.3). Analysis using the Mann-Whitney U test indicated a statistically significant difference between the two groups (p = .019). These findings demonstrate that blended microlearning effectively enhances students' cognitive understanding, practical skills, and learning motivation in geography practicums. Therefore, this study recommends adopting microlearning-based blended strategies as a low-cost, feasible instructional alternative for schools with limited educational resources.